2012
DOI: 10.4103/0019-5545.94640
|View full text |Cite
|
Sign up to set email alerts
|

Addition of home-based cognitive retraining to treatment as usual in first episode schizophrenia patients: A randomized controlled study

Abstract: Objective:We examined the effectiveness of a 2-month-long home-based cognitive retraining program together with treatment as usual (TAU; psychoeducation and drug therapy) on neuropsychological functions, psychopathology, and global functioning in patients with first episode schizophrenia (FES) as well as on psychological health and perception of level of family distress in their caregivers.Materials and Methods:Forty-five FES patients were randomly assigned to either treatment group receiving home-based cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Across all included studies there were a total of 1580 participants with a median sample size of 101, ranging from 45 to 326. Five studies, reported in six papers, were conducted in China [ 35 40 ], two studies were conducted in India [ 41 , 42 ] and Iran [ 43 , 44 ], one study, reported in two papers, was conducted in South Africa [ 45 , 46 ], and one study was conducted in Turkey [ 47 ]. All studies were conducted in upper-middle income countries apart from the two studies based in India, which is classified by the World Bank as lower-middle income.…”
Section: Resultsmentioning
confidence: 99%
“…Across all included studies there were a total of 1580 participants with a median sample size of 101, ranging from 45 to 326. Five studies, reported in six papers, were conducted in China [ 35 40 ], two studies were conducted in India [ 41 , 42 ] and Iran [ 43 , 44 ], one study, reported in two papers, was conducted in South Africa [ 45 , 46 ], and one study was conducted in Turkey [ 47 ]. All studies were conducted in upper-middle income countries apart from the two studies based in India, which is classified by the World Bank as lower-middle income.…”
Section: Resultsmentioning
confidence: 99%
“…Fears of “gossip and ridicule” in the community were common in the collaborative community-based care programme in India [ 23 ]. An anecdotal report from another Indian study of home-based cognitive retraining suggested that high dropout rates could be due to families’ fear of stigma associated with attending the psychiatric hospital where the study was located [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intensive CR protocols available in developed countries are difficult to implement in India in view of the multiple ethnic groups, cultural practices and above all, a scarcity of mental health professionals. Thus, it is important to develop innovative CR approaches that can be implemented with brief training (Hegde et al, 2012). CR research in India is gathering momentum.…”
Section: Discussionmentioning
confidence: 99%
“…Hegde reported a 2 month home based CR program, based on a prior pilot study (Hegde et al, 2007, 2012). She developed booklet based tasks to be practiced weekly as an easier and cheaper alternative to one on one CR programs (n = 45 first episode schizophrenia patients, duration of illness less than two years, 12 subjects and 11 controls for final assessment) (Hegde et al, 2012).…”
Section: Home Based Unsupervised Cognitive Retrainingmentioning
confidence: 99%
See 1 more Smart Citation